INTERNAL COMBUSTION ENGINE INTAKE MANIFOLD AIR FLOW OPTIMIZATION - ARUMUGAM, UVANISWARAN (IRC, 2017)
This project is focused on the optimization of intake manifold for better engine performance. The main factor that is tested is intake manifold runner’s length and its effect on the engine efficiency. The experiment for varying runner length is done by means of computational fluid dynamics using the ANSYS Fluent. The effectiveness of the intake manifold for in-cylinder air motion is observed using ANSYS IC Engine solver. The tested engine is 1.8L Ford Endura Diesel .The current intake manifold is designed to serve a limited range of engine speed and have an average air flow and pressure pulse distribution. The experiment is setup to test the manifold performance with varying runner length at three different engine speeds, ranging from 2500rpm to 4500rpm. The calculation for runner length is done using different resonance and pressure wave tuning theories and the best theory is selected by head-on comparison between them. A new design for the intake manifold is made compromising three stages of varying runner length tuned to give peak torque at the particular engine speed. Other factors that will be improved from the original design will be the plenum volume which is obtained using the same theory as the runner length and angle of the plenum for even pressure pulse distribution between the intake runners which is determined using ANSYS Fluent. The result sees the torque curve graph improved from the standard engine specification and a higher power yield